The Effect Of Work Life Balance And Compasation On Peformance (Cencus On Non ASN Employees BPBD Tasikmalaya) - Novi Auliya; Arga Sutrisna; Kusuma Agdhi Rahwana (Penerbit Jurnal Indonesia, 2022)
Human resources have a very important role in achieving company goals. Work life balance can be unbalanced due to long working hours compared with personal time, so it can make employees vulnerable to have a decrease in performance. Different compensation for each employee can cause a decrease in performance because with giving the same workload, it can make the employees feel less valued and feel that workload who given is not commensurate with compensation and performance generated by employees.This study aims to determine the description of Work Life Balance, Compensation, and Performance on Non ASN Employees at BPBD Tasikmalaya. The analytical method used is multiple linear regression analysis. The results of hypothesis testing found that Work Life Balance and compensation has a Simultaneous significant effect on employee performance at BPBD Tasikmalaya, but the Work Life Balance partially has no significant effect on Employee Performance at BPBD Tasikmalaya. Therefore, it is suggested for BPBD should be able to adjust given the workload to employees so they can divide time with personal lives and the time they spend is not used too much in the office so a decrease in employee performance can be minimized.